An adaptive pulse-width modulation scheme for DC-AC converters in electric vehicles - Tan, Raymond Kang Zhi (2016)
Machines such as AC motor, Solar panel circuit and wind turbine specification have been improving each year such as high power rating and high output voltage to the load. It is necessary to use inverters with high advanced pulse width modulation (PWM) scheme to minimize power losses and harmonic distortion in order to provide better efficiency. With the improvement of power electronic devices, the three phase voltage source inverter is capable of converting DC power to AC power with the function of variable magnitude and variable frequency.